High Prescribing: A Case Study of High-Potency Medicinal Cannabis Inducing Psychosis - Richard C. J. Bradlow; Sophie Wright; Anamaria Szrajbman Vaz Da Silva; Ferghal Armstrong (Case Reports in Psychiatry)
Conclusion: There are clear dangers to overprescribing medicinal cannabis and the care that needs to be taken by prescribers to avoid them. There is a need for a change in the regulation of cannabis prescribing in Australia. Further research is warranted on the effects of the increase in prevalence of cannabis prescribing.